2001
DOI: 10.1046/j.1365-2265.2001.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sandostatin® LAR® on sleep apnoea in acromegaly: correlation with computerized tomographic cephalometry and hormonal activity

Abstract: The findings demonstrated that there was correlation between sleep apnoea severity and soft tissue overgrowth at the upper airway region in acromegaly. They also suggest that Sandostatin LAR improved obstructive sleep apnoea in acromegaly, and the effect might be partly mediated via a reduction in upper airway soft tissue, in particular that of the tongue, concomitant with a reduction in GH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 21 publications
4
42
0
7
Order By: Relevance
“…Although it has previously been described that patients with the central form of SA have significantly higher GH and IGF-I levels than those with obstructive disease (6), in this patient GH and IGF-I levels were lower than the respective maximum levels of the group. Also, we confirmed previous reports that suggested OSA to be the most prevalent form of sleep-disordered breathing in acromegaly (95.3%, nZ21) (2,6,19). Several anatomical skeletal abnormalities that predispose to OSA, such as dorsocaudal rotation of the mandible, increase in facial height, and narrowing of the depth of the bony framework of the nasopharynx, have been identified in patients with acromegaly (20)(21)(22).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although it has previously been described that patients with the central form of SA have significantly higher GH and IGF-I levels than those with obstructive disease (6), in this patient GH and IGF-I levels were lower than the respective maximum levels of the group. Also, we confirmed previous reports that suggested OSA to be the most prevalent form of sleep-disordered breathing in acromegaly (95.3%, nZ21) (2,6,19). Several anatomical skeletal abnormalities that predispose to OSA, such as dorsocaudal rotation of the mandible, increase in facial height, and narrowing of the depth of the bony framework of the nasopharynx, have been identified in patients with acromegaly (20)(21)(22).…”
Section: Discussionsupporting
confidence: 90%
“…Several anatomical skeletal abnormalities that predispose to OSA, such as dorsocaudal rotation of the mandible, increase in facial height, and narrowing of the depth of the bony framework of the nasopharynx, have been identified in patients with acromegaly (20)(21)(22). Other studies suggested that upper airway narrowing caused by changes in pharyngeal soft tissues may play a more relevant role in the development of OSA in acromegalic patients than skeletal anomalies (19,22,23). In addition to adenoid, uvular, and tonsilar hypertrophy, macroglossia also narrows pharyngeal airway space (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apnea-hypopnea index improved in 55% and snoring episodes were reduced in 66% of patients (Ip et al, 2001). …”
Section: Sleep Apnea-reductionmentioning
confidence: 94%
“…For instance, some studies showed significant improvement after pituitary surgery [7] or somatostatin analogues [8,9], while others observed that SAS persisted after recovery of acromegaly in a relatively high percentage of patients, despite a potential association with IGF-I levels and disease duration [1]. In their longitudinal study, Castellani et al noted how active acromegalic patients who achieved biochemical control, regardless of how they did so (surgery, radiotherapy and/or medical therapy), experienced improvement of their sleep disorder.…”
mentioning
confidence: 99%